Variable Renewable Energy Locational Study - World Bank (World Bank, Washington, DC, 2021)
The objective of this study is to identify the most suitable zones for solar and wind power development in Pakistan. The study was carried out by a team of expert consultants over a period of 18 months in collaboration with all the key federal organizations in power system planning, led by the National Transmission and Despatch Company (NTDC) as the primary technical counterpart, with the findings reported to the Ministry of Energy (Power Division). This study confirms that Pakistan has excellent resources for economically viable solar power and wind power generation, both of which are mostly untapped so far. Especially noteworthy is the huge potential in western Balochistan for both solar and wind power, which will require significant grid infrastructure investments to be exploited. Further excellent areas with large solar potential are to be found in Sindh and southern Punjab, and the wind corridors in southern Sindh around Jhimpir and Gharo still have more potential than what has been developed so far.